Facile mechanosynthesis of amorphous zeolitic imidazolate frameworks. - Bennett, T; Cao, S; Tan, J; Keen, D; Bithell, E; Beldon, P; Friscic, T; Cheetham, A (2011)
A fast and efficient mechanosynthesis (ball-milling) method of preparing amorphous zeolitic imidazolate frameworks (ZIFs) from different starting materials is discussed. Using X-ray total scattering, N(2) sorption analysis, and gas pycnometry, these frameworks are indistinguishable from one another and from temperature-amorphized ZIFs. Gas sorption analysis also confirms that they are nonporous once formed, in contrast to activated ZIF-4, which displays interesting gate-opening behavior. Nanoparticles of a prototypical nanoporous substituted ZIF, ZIF-8, were also prepared and shown to undergo amorphization.